PKM PUSKESMAS CURUGBITUNG: PENINGKATAN KUALITAS TUMBUH KEMBANG ANAK USIA DINI BERBASIS WEBSITE UNTUK MENDUKUNG PENCAPAIAN SDGS POIN 4 - Permadi, Agung; Elistania, Elistania (Universitas Mercu Buana, 2024)
Lebak Regency has the second-highest prevalence of stunted toddlers in Banten, at 27.3%. The causes are not only malnutrition among pregnant women and toddlers but also a lack of maternal understanding of parenting practices that support the development of early childhood (0-6 years). Child development encompasses physical, cognitive, social, and emotional changes from birth to adulthood. At the Curugbitung Public Health Center (Puskesmas), midwives have not been equipped with comprehensive knowledge about child development, such as the Stimulation, Detection, and Early Intervention of Child Development (SDIDTK) program from the Indonesian Ministry of Health. The focus of midwives has remained limited to the 'Growth' aspect, such as height and weight, without considering the 'Development' aspect, which includes cognitive, social, emotional, and language development. Additionally, midwives are unable to provide age-appropriate developmental stimulation due to limited knowledge, time, and facilities. The solution offered by the Community Service team (PKM) from the International Relations Study Program of Universitas Budi Luhur is training to improve the quality of early childhood development based on a website to support the achievement of SDGs goal 4. This training aims to enhance midwives' knowledge and skills in early childhood care and development, with a holistic and integrative website-based learning module. This module facilitates midwives in providing counseling to parents, thereby improving the quality of early childhood education. The outcome of this activity is an increase in knowledge, skills, and the quality of health services, as well as the transfer of knowledge and technology to the community of Curugbitung, Lebak, Banten.